JOSÉ: UM RUBEM FONSECA ENTRE O EU REAL E O EU FICCIONAL - Araujo, Caroline Wilt (2014)
The dissertation aims to investigate evidence that José (2011), Rubem Fonseca work it is a autoficcional work. To this end, the work is divided into three chapters: the first search limits and origins of the term autofiction examining its principle based on another well known term which is the autobiography; the second chapter is focused on the analysis of the work of Rubem Fonseca as a whole, its main features, everything that makes Rubem Fonseca an author recognized for his work with language; finally, the last chapter is devoted to the study of the book José, in which is trying to point out all the evidence that this work it is an autofiction.